2017
DOI: 10.5424/sjar/2017151-10151
|View full text |Cite
|
Sign up to set email alerts
|

Explaining food insecurity among indigenous households of the Sierra Tarahumara in the Mexican state of Chihuahua

Abstract: Numerous studies have analyzed the factors that determine food security and explored the problem from regional or national points of view. However, there has been less research targeting an understanding of the food security problem at the household level in specific rural locations like indigenous communities. Indigenous groups are recognized as priority groups in Mexico, because they live in a situation of poverty. For this reason, the objective of this research was to investigate the determinants of food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In general, governments indeed recognize the role that agriculture has in stimulating economic growth and reducing rural poverty [72]. Therefore, the authorities should develop sustainable agriculture and safety nets for the most vulnerable sections of rural populations [26], as agriculture is one of the least-productive sectors but typically involves obtaining food from one's own production and/or subsistence farming [15,73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, governments indeed recognize the role that agriculture has in stimulating economic growth and reducing rural poverty [72]. Therefore, the authorities should develop sustainable agriculture and safety nets for the most vulnerable sections of rural populations [26], as agriculture is one of the least-productive sectors but typically involves obtaining food from one's own production and/or subsistence farming [15,73].…”
Section: Discussionmentioning
confidence: 99%
“…If there is consistency in the quantified responses, then σ t 2 will be relatively large, which will lead to α tending to one. Otherwise, the random answers will make σ t 2 comparable to the sum of the individual variances σ i 2 , which in turn will cause α to tend to zero [26,49].…”
Section: Evaluation Of the Reliability Of The Elcsa Using Cronbach's Alphamentioning
confidence: 99%
See 1 more Smart Citation
“…where i is the observation, β is the regression of coefficients for X, and ε is the identical and independent random error term [52,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Magaña Lemus D et al [88], found that younger, less-educated heads, headed by single, widowed or divorced women, rural and lower income households were more food insecure in Mexico. Cordero Ahiman OV et al [89], point out that income, consumed seed stock, maize production, casual employment, household size, education, access to water facilities, electricity, energy for cooking, land ownership, consumed seed stock, situation of poverty were critical factors which are affecting food security in Mexico.…”
Section: Association Of Fsi With Socio-economic Factorsmentioning
confidence: 99%